Survival, adverse events and management of silent in-hospital coronary bypass graft occlusion - Salikhanov, Islam; Koechlin, Luca; Gahl, Brigitta; Voehringer, Luise; Reuthebuch, Oliver; Dimanski, Daniel; Mawad, Brian M; Berdajs, Denis (Open heart, 2025)
ObjectivesTo assess mid-term outcomes in patients with early silent coronary bypass occlusion.Methods292 consecutive patients who underwent isolated coronary artery bypass grafting (CABG) between July 2021 and December 2023 were included in this prospective cohort study. Silent CABG occlusion was defined as a bypass occlusion detected by coronary CT before discharge and without clinical suspicion of perioperative myocardial infarction. The primary endpoint was the incidence of angina-related rehospitalisation and coronary revascularisation during the follow-up. The secondary endpoint was the incidence of major adverse cardiovascular and cerebrovascular events, defined as a composite of all-cause mortality, myocardial infarction and stroke.ResultsThe mean age was 67±9.5 years, with 85.3% (n=249) being male. Early silent occlusion was identified in 25 patients (8.5%). The median hospital stay was longer in the occlusion group with 10 days (IQR 8.0–12.0), versus 8.0 days (IQR 7.0–9.0) in the non-occlusion group (p<0.001). The median follow-up duration was 14.5 (IQR 13.3–16.5) months. The incidence of angina-related rehospitalisation and revascularisation was significantly higher in patients with graft occlusion (p<0.01). Cox proportional hazards regression identified graft occlusion as a strong predictor of rehospitalisation (HR=8.55, 95% CI: 3.23 to 22.64; p<0.001) and reintervention (HR=15.12, 95% CI: 4.89 to 46.74; p<0.001), indicating nearly a 9-fold higher risk of rehospitalisation and a 15-fold increased hazard of reintervention.ConclusionIn-hospital silent graft occlusion following CABG is associated with a higher incidence of angina-related rehospitalisation and revascularisation during mid-term follow-up.Trial registration numberNCT04595630.